Dualität aus gesetzlicher und privater Krankenversicherung überholt? - Klaus Jacobs; Friedrich Breyer; Jürgen Wasem; Anke Walendzik; Klaus-Dirk Henke (Wirtschaftsdienst, 2012)
Derzeit ist Deutschland europaweit das einzige Land mit einem Nebeneinander von zwei Systemen der Kranken-Vollversicherung. Die demographische Entwicklung verbunden mit einer fragwürdigen Akquisitionsstrategie, die Finanzkrise sowie die Einführung der Versicherungspfl icht hatten vor allem die privaten Versicherungen in Bedrängnis gebracht. Die Autoren plädieren hier für unterschiedliche Wege in Richtung eines einheitlichen Krankenversicherungssystems in Deutschland. – – The present division between statutory and private health insurance in Germany (GKV and PKV) is hard to justify. If it is the goal to include the whole population in the GKV eventually, one author states that the only legal way is to change its financing from wage-based contributions to a per-capita amount, which would generally reduce incentives to join the PKV. Possible reform alternatives for the financing of health insurance are analysed by another article according to the following principal questions: Are they able to raise sufficient funds and allocate them efficiently? How does that affect employment and distributive justice? These questions can be used to benchmark various insurance models, i.e. citizens insurance, citizens private insurance and premium models. Another article focuses on a non-profit private legal framework, e.g. a co-operative or a limited society.
Keywords: H51; I18; 330; Gesetzliche Krankenversicherung; Private Krankenversicherung; Gesundheitsreform; Wettbewerb; Solidarität; Gesundheitsfinanzierung; Deutschland